Tensions within management roles in healthcare organisations - Scott, Anne; Timmons, Stephen (RCN Publishing, 2017)
Aim: This article reports the results of a study that gives an insight into ward leaders’ perspectives of their leadership role and explores how they deliver leadership at ward level within organisational constraints and processes. Previous studies have been evaluations of clinical leadership in general, or literature reviews of the ward leader role. The aim of this study was to examine the leadership role of ward sisters and to understand how they lead improvements in quality of care on their wards.